Acute intermittent porphyria: Diagnosis per chance - Soundravally R; Goswami K; Nandeesha H; Koner B; Sethuraman K (Wolters Kluwer Medknow Publications, 2008)
Objectives: To report a case of acute intermittent porphyria (AIP) diagnosed by chance during routine investigations. Clinical Presentation and Intervention: A 21-year-old female presented with vague gastrointestinal symptoms. Upon admission, she was disoriented. Later she developed generalized seizures and was treated with phenytoin, but the condition worsened. Upon investigation, her liver function, renal function, blood sugar level and electrolytes were within normal limits. When kept for routine laboratory testing, the color change in urine prompted us to investigate for porphyria. It was positive for phorphobilinogen (PBG) and urophorphyrin. Since AIP had been diagnosed, the initial treatment with phenytoin was discontinued with a favorable outcome. A screening test for PBG in urine by Ehrlich′s reagent was performed on the patient′s mother and was positive. Conclusion: A high degree of suspicion at the laboratory can also determine the diagnosis of AIP, which is often missed by the clinician.